Development and Rasch Validation of a Climate Change-Based Test to Measure Senior High School Students’ Numeracy Literacy - Via Aini; Kusnadi Kusnadi; Topik Hidayat; Lilit Rusyati (Universitas Syiah Kuala, 2026)
The increasing availability of climate change-related data and the growing emphasis on data-based decision-making underscore the importance of numeracy literacy in education. Assessment instruments that integrate real-world issues, such as climate change, are needed to evaluate students’ ability to interpret, analyze, and reason with quantitative information. This study developed and validated a climate change-based numeracy literacy test for senior high school students. The instrument consisted of 36 multiple-choice items developed by aligning the PISA 2022 numeracy framework with selected climate change scenarios. Content validity was examined through expert judgement using Aiken’s V, while construct validity and reliability were analyzed using the Rasch measurement model. Data were obtained from 65 eleventh-grade students at a public senior high school in Lampung Province, Indonesia. The content validity results showed that all 36 items were classified as highly valid. Rasch analysis showed that 33 items (91.7%) conformed to the model expectations, supporting the construct validity and unidimensional structure of the test. The instrument demonstrated good item reliability (0.85–0.87) and fair person reliability (0.70–0.73), indicating that it is suitable for group-level assessment. The findings indicate that the instrument can be used to assess climate change-based numeracy literacy, although several items require further refinement